Temperature and Humidity Relationships of Scaled Quail Nests in Southern New Mexico - Carol A. Evans; Sanford D. Schemnitz (National Quail Symposium Proceedings, 2017)
We observed unmarked and radio-marked (20 females/1994; 9 females and 11 males/1995) scaled quail (Callipepla squamata) during the nesting season in the Chihuahuan Desert of southern New Mexico. In 1994, pairing was completed by early April. Clutch size averaged 13.8 ± 1.7 (n = 7). Nests were located an average 216 ± 13.8 m from permanent water. All 97 chicks disappeared from r dio-marked pairs by 16. July. In 1995, all radio-marked females and 6 of the radio-marked males were paired by mid-April. Clutch size averaged 10.3 ± 1.3 m nests (n = 8) that averaged 545 ± 1.7 m from permanent water. Almost half of the hatched chicks (49.6%) fledged in 1995. Nest temperature never exceeded 34°C, while ambient temperatures reached ?43°C. Nest humidity averaged 23%, while ambient humidity averaged 12%.